Immunohistochemical Staining Properties of Osteopontin and Ki-67 in Feline Meningiomas - Gabriele Gradner; Janina Janssen; Anna Oevermann; Alexander Tichy; Stefan Kummer; Stefanie Burger; Ingrid Walter (Animals)
The high recurrence rate of feline meningioma despite the generally benign histomorphology warrants additional markers of clinical aggressiveness. The Ki-67 index is commonly used as prognostic marker for meningioma recurrence in people. Osteopontin (OPN) is a protein involved in tumor progression and may be a potential malignancy marker. To date, osteopontin expression has not been investigated in feline meningioma. The aim of this study was to evaluate the extent of Ki-67 and osteopontin immunostaining of feline meningioma and to find possible associations with WHO (World Health Organization) grades and subtypes. Fifty-three feline meningioma samples were graded according to the human WHO classification and underwent immunohistochemical examination for Ki-67 and OPN. Fifty samples were classified as WHO grade I and three as WHO grade II. The mean Ki-67 ratio was 9.19 ± 9.47. Osteopontin expression was correspondingly high with a mean OPN IHC score of 150.17 (0–242.8), and a median Allred score of 7 (0–8). There was no significant correlation with Ki-67 index, osteopontin expression, WHO grades, or subtypes. The overall high expressions of osteopontin and Ki-67 may help explain the tendency for recurrence of feline meningioma. The human WHO grading system may not be sufficient to accurately estimate the clinical behavior of meningioma in this species.